Dinamika Psikologis Remaja Di Panti Asuhan: Studi Fenomenologi - Maria Setiarini; Kalis Stevanus (DIEGESIS: Jurnal Teologi Kharismatika, 2021)
This paper is intended to describe the psychological dynamics of adolescents living in orphanages. How are the psychological dynamics of adolescents in living their adolescence without direct guidance and affection from their parents. This study uses a qualitative approach with phenomenological methods. From the results of this study, it was concluded that there were significant differences in the psychological dynamics of adolescents living in orphanages because they had to be entrusted by parents with adolescents living in an orphanage because of their own desires. Psychologically, adolescents who are forced to live in orphanages tend to close themselves off from their environment. Meanwhile, adolescents who live in homes because of their own desires, they tend to be more open to their environment. In addition, the age factor when they enter the orphanage environment also affects their psychological dynamics. Those who enter the orphanage when they are children tend to be more adaptable. Conversely, those who enter when they are teenagers tend to have more difficulty adapting. Therefore, it is hoped that the management of the orphanage can understand the psychological dynamics of adolescents and their struggles, so that it can help them to live adolescence properly, even without the presence of their biological parents.